Experimental study on the splitting tensile failure of a carbon nanotube-modified fly ash foamed concrete filler - Shukun Zhang; Xinghui Wu; Peng Jiang; Haohao Wang; Shuai Wang; Haojie Yang; Lu Lu (Scientific Reports)
Abstract To study the enhancement effect of carbon nanotubes (CNTs) on the splitting tensile properties of foamed concrete backfill in which cement and fly ash were used as the cementitious materials and natural sand was used as the aggregate, specimens of CNT-modified foamed concrete backfill were prepared. Brazilian splitting tests were used to investigate the splitting tensile strength of the CNT-modified foamed concrete backfill, and the digital speckle correlation method was used to analyze the stress field characteristics and crack expansion law of the specimens during splitting tensile testing. The stress–strain characteristics and energy dissipation laws of the backfill were studied at various static loading rates, and a relationship between the splitting tensile strength, ultimate strain, and loading rate was established. The results showed that at the optimum CNT content of 0.05%, the peak strength and ultimate strain of the modified foamed concrete backfill increased by an average of 67.2% and 21.7%, respectively. Moreover, after modification with CNTs, the foamed concrete backfill was less likely to develop strain concentration areas before reaching peak strength. The triangular stable loadbearing structure formed by the modified foamed concrete backfill after splitting caused the end of the stress–strain curve to exhibit varying degrees of “backlash”. For the CNT-modified foamed concrete backfill, the peak strength correlated logarithmically with the loading rate, while the ultimate strain correlated as a power function of the loading rate. At a low loading rate, the CNT-modified foamed concrete backfill dissipated less energy, and the reverse was true for higher rates.